NOBCChE Newsletter, Volume 1, Number 1 (National Organization for Black Chemists and Chemical Engineers, 1979)
The inaugural issue of the National Organization for the Professional Advancement of Black Chemists and Chemical Engineers (NOBCChE) Newsletter, published December 1979.
Keywords: National Organization for Black Chemists and Chemical Engineers; African American chemists; African American engineers; Chemical engineers; Chemists; Newsletters; Periodicals; Scientists, Black; African American scientists